5-ALA-Induced Fluorescent Urine Cytology in Comparison with Conventional Cytology, BTA-TRAK, and NMP-22 Tests in the Diagnosis of Bladder Cancer - Rajendra B Nerli; Shadab Rangrez; Shridhar C. Ghagane; Parth Lalakia; Shoubhik Chandra; Shreya Chandra (Brazilian Journal of Oncology)
Introduction To assess the sensitivity fluorescent urine cytology induced by 5-aminolevulinic acid (5-ALA) in the diagnosis of bladder cancer and to compare the sensitivity and specificity with currently available markers approved by the United States Food and Drug Administration (FDA), bladder tumour antigen (BTA-TRAK, Bard Diagnostic Sciences, Redmond, WA, United States) assay based on enzyme-linked immunosorbent assay (ELISA), nuclear matrix protein 22 (NMP-22), and conventional cytology.